Por uma formação menor na licenciatura em Física: resistências, singularidades e criações no processo formativo - Moraes, João Paulo Ramos de (Universidade Federal de São Carlos, 2025)
This dissertation investigates the phenomenon of persistence in Physics Teacher Education programs through the lens of subjectivity, shifting the focus from dropout as a punctual event to a continuous and relational process. Inspired by the Philosophy of Difference, particularly the works of Deleuze, Guattari, and Foucault, this study understands persistence not as an individualized trajectory but as a collective assemblage shaped by power relations, affects, and resistance practices. Initially, we analyze the historical development of Physics Teacher Education programs in Brazil and academic research on university dropout, identifying how the field has approached these issues and the limitations of these perspectives. We then discuss the production of subjectivities in higher education and the possibilities of deterritorializing these forms of existence within the academic space. The research adopts a self-reflective and experimental approach, incorporating the analysis of an autobiographical narrative produced during the investigation. Based on this, we develop the concept of Minor Formation, a way of inhabiting the university that challenges normative structures and creates space for singular experiences of persistence. This dissertation does not aim to provide universal solutions but rather to offer clues on how collective processes, support networks, and creative practices can help reshape university persistence and expand the possible ways of existing within Physics Teacher Education programs.
For a minor formation in Physics: resistances, singularities and creations in the formation process
Keywords: Permanência universitária; Subjetividade; Formação menor; Filosofia da diferença; Licenciatura em física; University persistence; Subjectivity; Minor formation; Philosophy of difference; Physics teacher education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM